Kontrol Kelembaban Pada Media Budidaya Cacing Lumbricus Terrestris Dengan Metoda Fuzzy - Bimantara, Raka Pinudya; Radianto, Donny; Fitri; Dwi Risdhayanti, Anindya (Journal of Applied Smart Electrical Network and Systems, 2023)
Lumbricus worm is one of the cultivated animals wich contain high protein. Other benefit of lumbricus worm is can be medicine for tipes. In worm cultivation there are parameters that we have to control. These parameter is moisture of media and air temperature around cultivation media. Based on that problem, this plant is designed to control moisture media of cultivation and air temperature with fuzzy metode. The component that use in this plant is soil moisture sensor, DHT11, Arduino, and pump dc for actuator. The mechanism of this plant in these sensor will read parameter and send the data to Arduino, the data will be processed with fuzzy metode, the output of fuzzy metode is timer that use to trigger the pump on and off. The result of final tes is the plant can control moisture of media cultivation and air temperature properly. The final weight of worm from harves is increase 40% from the seed dispersal. From that case can conclude that implementation of this plant is give real positif affect to harves of lumbricus terrestris worm